Innovating Education Online Crafting Dynamic Learning Environments - Arifin, Agus; Ruhiat, Yayat; Nulhakim, Lukman (Cetta: Jurnal Ilmu Pendidikan, 2024)
Web-based learning environments have changed the traditional way of teaching to be more interactive and adaptive. However, there are challenges in making e-learning designs effective, aesthetically appealing and easy to use, and capable of improving learning outcomes and changing learning behaviors. This study investigates the influence of web-based learning environments on STEM education, focusing on the aesthetic appeal, user-friendliness and appropriateness of the visual design of mobile websites. The research objective is to evaluate the effectiveness of e-learning designs that include the incorporation of creativity, structured approaches, and evidence-based practices to improve learning outcomes and change learning behaviors. The research methodology involved literature analysis, content organization, and integration of interactive instructional design and multimedia elements. Merrill's Principles of First Instruction and the SAM Model were used as the basis of learning theory. Evaluation was conducted on modularity, scalability, codebase security, and user experience through navigation, intuitiveness, accessibility, and overall user happiness. The GUI design is accessible via PC/Laptop and Android and iOS-based mobile devices. The results show that comprehensive instructional design and the use of multimedia learning can improve learning outcomes. The integration of multimedia content such as videos, images, and interactive simulations within the web learning environment can increase engagement and facilitate effective learning. media experts and programming experts evaluated the visual and technical aspects of the website, providing recommendations to improve usability and performance. users also evaluate the website's ability to facilitate stem learning and report usability issues that could be improved. regular performance monitoring and testing, along with implementing best practices, can improve website quality and performance. fixing usability issues and improving website performance will provide a better learning experience for users.